English Language MGMP Empowerment Management for Senior High Schools: Strategic Analysis of Improving The Professional Competence of Senior High School Teachers in Pemalang Regency - Mustaidah, Mustaidah; Wuryandini, Endang; Muhtarom, Muhtarom (Dinasti Publisher, 2025)
This study aims to determine empowerment management English Subject Teachers' Conference (MGMP) for Senior High Schools (SMA) in Pemalang Regency as a forum for continuing professional development to improve the professional competence of high school teachers. The main objective is to describe and analyze the effectiveness of MGMP empowerment management as seen through four main functions. POAC (Planning, Organizing, Actuating, and Controlling). Using a qualitative approach with a case study type, data was collected through participant observation, in-depth interviews, and documentation studies. The results of the study show that effective management characterized by strong synergy across POAC functions. Planning is participatory and based on authentic, evidence-based needs identified through polling WAG and needs analysis checklist. Organizing featuring a competency-based structure, transparent financial management, and institutional collaboration strong relationships with external parties (e.g., universities) formalized through MoU. Implementation (Actuating)driven by humanistic and collaborative leadership and implemented through workshop which emphasizes ands-on practice and simulation(70% of activity time), which leads to successful knowledge transfer confirmed through classroom observations and post-program learning plan analysis. Finally, Control (Controlling)is a digital and data-based system that utilizes real-time monitoring (real-time) through dashboard Google Drive and tiered evaluations that focus on measurable impact This empowerment management model has been proven to significantly support the improvement of professional competence, foster sense of ownership among teachers, and resulting in real changes in teaching practice, particularly in designing and implementing authentic project-based assessments. This highly effective and sustainable model worthy of replication.